Novel Researched Herbal Sunscreen Cream SPF Determination by In-Vitro Model - Pandey, Prateek; Sharma, Anil; Sharma, Hariom; Vyas, Girish Kumar; Sharma, Manmohan (Asian Journal of Pharmaceutical Research and Development, 2023)
INTRODUCTION: Researchers' interest in creating novel cosmetic formulations has increased due to consumer interest in herbal cosmetics and increased patent activity. The rights of indigenous traditional knowledge and benefit sharing are also safeguarded under IPR. OBJECTIVE: To formulate and evaluate herbal sunscreen with determination of Sun Protection Factor (SPF) and anti-oxidant activity. To compare Sun Protection Factor of developed formulation with marketed formulation. METHOD: The formulation was developed according to the prepared formula. And multiple tests were done for evaluation i.e., physical observation, spreadability, extrudability, occlusion study, stability study and SPF determination. All the evaluations were found satisfactory. Characterisation of SPF was calculated according to the and UV-Vis Spectrophotometer (LABMAN Scientific instruments Pvt. Ltd.). RESULTS:The synergistic activity of all herbal compounds utilized in herbal sunscreen formulations, such as Cucumis sativus, Solanum Lycopersicon, and Aloe barbadensis Efficacy of photoprotection found in following order Marketed formulation > F3 > F2 > F1. For prepared formulation F3 provided better results in comparison to Formulation1 and Formulation 2. Formulation 3 was compared with marketed preparation and it showed good SPF value nearer to market preparation. Overall results were satisfactory. These results reveal that the prepared F3 herbal sunscreen have good SPF and good sun protection activity. CONCLUSION: Formulation 3, which consists of three formulations, has been found to be effective as sunscreen in every way. Since few people use sunscreen, there is a need to raise public knowledge of the risks associated with sun exposure as well as the advantages of using sun protection products on a regular basis to lessen these effects. This kind of research will be useful in offering consumers with an all-inclusive solution or product that will protect them from the damaging effects of sunlight.